Impact and feasibility of a tailor-made patient communication quality improvement programme for hospital-based physiotherapists: a mixed-methods study. Issue 2 (22nd April 2021) - Steenbruggen, Rudi A; van Heusden-Scholtalbers, Linda AG; Hoogeboom, Thomas J; Maas, Marjo; Brand, Paul; Wees, Philip van der
Abstract : Background: In tailoring a quality improvement programme for hospital-based physiotherapy, the original use of video recordings was replaced by using the tracer methodology. Objective: To examine the impact of a tailor-made quality improvement programme addressing patient communication on the professional development of hospital-based physiotherapists, and to evaluate barriers and facilitators as determinants of feasibility of the programme. Methods: A mixed-methods study was conducted. Participants were clustered in groups per hospital and linked with an equally sized group in a nearby hospital. Within the groups, fixed couples carried out a 2-hour tracer by directly observing each other's daily work routine. This procedure was repeated 6 months later. Data from feedback forms were analysed quantitatively, and a thematic analysis of transcripts from group interviews was conducted. Results: Fifty hospital-based physiotherapists from 16 hospitals participated. They rated the impact of the programme on professional development, on a scale from 1 (much improvement needed) to 5 (no improvement needed), as 3.99 (SD 0.64) after the first tracer and 4.32 (SD 0.63) 6 months later; a mean improvement of 0.33 (95% CI 0.16 to 0.50). Participants scored, on a scale ranging from 1 to 5 on barriers and facilitators (feasibility), a mean of 3.45 (SD 0.95) on determinants of innovation, 3.47 (SD 0.86) on probability to use and 2.63 (SD 1.07) on the user feedback list. All participants emphasised the added value of the tracer methodology and mentioned effects on self-reflection and awareness most. Conclusions: The tailor-made quality improvement programme, based on principles of the tracer methodology, was associated with a significant impact on professional development. Barriers and facilitators as determinants of feasibility of the programme showed the programme being feasible.